FINANCIAL INSTRUMENTS FOR BUSINESS GROWTH DURING ECONOMIC RECOVERY - Saitmuratov Saitmurat (Web of Journals Publishing, 2024)
This article explores the role of government financial instruments in promoting business growth during economic recovery, with a focus on tax incentives, subsidies, and public investments. Using examples from Uzbekistan and lessons from developed countries such as the United States, Germany, South Korea, and Japan, the article examines how these instruments enhance business liquidity, stimulate long-term growth, and mitigate the risks associated with economic downturns. The challenges in implementing these financial tools, including administrative inefficiencies and resource misallocation, are also discussed. Additionally, the article provides insights into best practices for maximizing the effectiveness of financial instruments in emerging economies.
Keywords: Financial instruments, economic recovery, business growth, tax incentives, government subsidies, public investments, liquidity, Uzbekistan, developed countries, economic policy, administrative challenges, infrastructure investment, fiscal policy.